A comprehensive reading of Psalm 137 - Simango, Daniel (Old Testament Essays, 2018)
The purpose of this article is to carry out a thorough exegetical study of Ps 137 in order to grasp its content, context and theological implications. The basic hypothesis of this study is that Ps 137 can be best understood when the text is thoroughly analysed. Therefore, in this article, Ps 137 will be read in its total context (i.e. historical setting, life-setting and canonical setting) and its literary genre. The article concludes by discussing the imprecatory implications and message of Ps 137 to the followers of YHWH.
free